Reemplazo hepático extracorpóreo no biológico: tipos e indicaciones - Gadano, Adrián; Rosa Diez, Guillermo; Grelon, Gustavo; Galdame, Omar; Marciano, Sebastián; Gianass, Sergio; Algranati, Salomón; Argibay, Pablo (Revista del Hospital Italiano de Buenos Aires, 2010)
.